Conceptual design methodologies appropriate to blended wing body aircraft with boundary layer ingestion - Gao, Ziang (Cranfield University, 2021)
Blended wing body aircraft equipped with boundary layer ingestion technology represent a paradigm leap in aircraft design, one that provides significant aerodynamic and environmental benefits while reducing fuel consumption. Although there are numerous advantages to this structure, there are also various issues that arise as a result of the highly integrated nature of the configuration and the disciplinary couplings that ensue. This project develops a conceptual design methodology appropriate to the blended wing body commercial passenger transport with boundary layer ingestion and applied this methodology into the Cranfield multidisciplinary design analysis and optimisation environment – GENUS. The GENUS framework integrates a variety of aerodynamic analysis tools, an efficient geometry parameterization method, a semi-empirical mass breakdown model, and an effective boundary layer ingestion analysis model to enable the synthesis of a realistic conceptual design and exploration of the design space for this novel class of aircraft. The comparative case studies of blended wing body airplanes and conventional airplanes in three different sizes find that the blended wing body is more advantageous at larger aircraft sizes, which achieve 10.4% reduction in fuel consumption for 14000km-mission-range, 555- passenger class and the benefit could be expanded to 16.9% with the application of boundary layer ingestion. The parameter sensitivity analysis shows that the central body sweep is a key parameter for the design of the blended wing body aircraft, and the optimal central body sweep with the minimum fuel consumption increases as the cruise Mach number increases. In the final optimisation part, the geometry at Mach 0.74 has the lowest fuel consumption, but the one at Mach 0.86 has the highest productivity. The optimised geometry with boundary layer ingestion leads to a 10.8% reduction in the fuel consumption but an 0.8% higher structure weight compared to the optimised geometry without boundary layer ingestion.
Zare Shahneh, Amir - Associate Supervisor
Keywords: Aircraft conceptual design; Multidisciplinary design optimisation; Blended wing body; Boundary layer ingestion; GENUS; central body sweep